Increasing the Role of Fostered Kader in the Stunting Prevention Program in the Boja 2 Community Health Center, Boja District, Kendal Regency - Ahmad Riadi; Riskiyana Sukandhi Putra; Arwani; Tri Wiji Lestari (Poltekkes Kemenkes Semarang, 2026)
Stunting is a condition of growth failure in children, characterized by impaired physical growth and cognitive development due to long-term chronic malnutrition. This condition occurs from the fetal period through early childhood, commonly referred to as the first 1,000 days of life. Preventing stunting requires the involvement of multiple stakeholders, including the active role of adolescents as agents of change within the community. This community service program aimed to enhance adolescents’ capacity for early detection of stunting and to strengthen collaboration with primary health centers in addressing stunting. The methods included health education, capacity building for adolescent cadres, and cross-sector collaboration with community health centers. The results showed that adolescent cadres, in collaboration with partners, were able to implement iron supplementation (iron tablets) programs for elementary, junior high, and senior high school students. In addition, adolescent cadres actively provided education to parents and adolescents on adequate nutrition and early stunting prevention. This program is expected to serve as a sustainable strategy to support the acceleration of stunting reduction in the community.